A qualitative exploration of multi-stakeholder perspectives of before-school physical activity - Woodforde, James; Kuswara, Konsita; Perales, Francisco; Salmon, Jo; Gomersall, Sjaan; Stylianou, Michalis (The international journal of behavioral nutrition and physical activity, 2024)
Engagement in before-school physical activity can potentially enhance health and learning-related outcomes for children and adolescents. However, influencing factors and stakeholder perceptions of before-school physical activity remain under-researched. This qualitative study aimed to examine stakeholder perceptions of: a) the suitability of the before-school segment for physical activity, b) barriers and facilitators associated with before-school physical activity, and c) strategies for schools to support before-school physical activity. Twelve focus groups and one interview were conducted with 38 participants from a range of school stakeholder groups-students, parents, teachers, school leaders, external physical activity providers, and school health and physical activity experts. Focus groups were analysed using template analysis, guided by a social-ecological model. Stakeholders perceived before-school physical activity as valuable, for reasons including perceptions of meaningful contributions to students' cognitive functioning, classroom behaviours, and wellbeing. Factors influencing before-school physical activity were identified across multiple social-ecological levels, including the critical role of school leadership support, availability of facilities, and provision of qualified supervision. Proposed strategies highlighted the need for sustainable design, contextual relevance, and community engagement in before-school initiatives. Additionally, communication of the manifold benefits identified by stakeholders was suggested as a means to drive support and engagement in before-school physical activity. This study provides insight for schools seeking to enhance opportunities for physical activity in the before-school hours and may inform future intervention research on the subject, taking into account its multi-faceted influences and the need for context-specific strategies.